Research Trends in Higher Education Digital Entrepreneurship Ecosystems: A Bibliometric Analysis - Wahyudi, Stephanus Eko; Baihaqi, Imam; Arvitrida, Niniet Indah (Jurnal Entrepreneur dan Entrepreneurship, 2021)
Entrepreneurship is considered as one of the solutions to support the economy of a country. The rapid development of information and communication technologies introduces opportunities to create new digital ventures. Many giant companies successfully grow their business exponentially, although many of them do not even own products. Many countries, including Indonesia, are keen to support and encourage more people to build digital startups. There are many successes story about entrepreneurship ecosystems that contributes to the success of digital ventures. One of the critical factors of the success of an ecosystem is the availability of campuses that support innovations and talents. Thus, it is critical to find the optimum digital entrepreneurship ecosystem for education to produce new and sustainable digital entrepreneurs—this research attempt to find out the research trends in digital entrepreneurship ecosystems in higher education. The method used in this research was bibliometric analysis using three software, including Publish or Perish, Mendeley Reference Manager, and VOSviewer. The results are presented in a graphical network map of terms in several relevant keywords. This research concludes that while there are many studies about the entrepreneurship ecosystem during 2015-2021, few studied the development of digital entrepreneurship ecosystems in higher education.